Pengaruh Model Teams Games Tournament Berbantuan Multimedia Interaktif Terhadap Hasil Belajar Siswa SD - Linda, Pance Yunita Nova; Yusnia, Yusnia; Agusdianita, Neza; Heryanto, Debi (Universitas Sebelas Maret, 2025)
This study aims to determine the effect of using the Teams Games Tournament model assisted by interactive multimedia on the learning outcomes of elementary school students in cluster 9 (nine) Bengkulu City. This research is a quantitative using a quasy-experimental research method and The Matching Only Pretest-Posttest Control Group Design. The population in this study were grade IV students of cluster XII Bengkulu City. While the samples were IVA class students of SDN 60 Bengkulu City as the experimental group and IVB class students of SDN 81 Bengkulu City as the control group obtained through cluster random sampling. The techniques used in this study were pre-test and post-test designed in the form of 10 multiple-choice questions. The results of hypothesis test in the experimental group showed that the tcount value using Equal Variences Assumed = 5.615 and the Sig value. (2-tailed) value is 0.000 and the ttable distribution value is 1.692, so that tcount value > ttabel (5.615 > 1.692) and Sig. (2-tailed) 0.000 <0.05. This data shows that there are differences in learning outcomes in the experimental group and control group caused by the treatment of the two different groups. Based on this, it can be concluded that there is an effect of the Teams Games Tournament model assisted by interactive multimedia on the learning outcomes of the knowledge aspects of elementary school students in cluster 9 (nine) Bengkulu City.Penelitian ini bertujuan untuk mengetahui pengaruh model teams games tournament berbantuan multimedia interaktif terhadap hasil belajar siswa SD gugus XII Kota Bengkulu. Penelitian ini merupakan penelitian kuantitatif dengan metode penelitian quasy experiment dan jenis desain The Matching Only Pretest-Posttest Control Group Design. Populasi dalam penelitian ini adalah siswa kelas IV gugus XII Kota Bengkulu. Sedangkan sampelnya adalah siswa kelas IVA SDN 60 Kota Bengkulu sebagai kelompok eksperimen dan siswa kelas IVB SDN 81 Kota Bengkulu sebagai kelompok kontrol yang diperoleh melalui cluster random sampling. Teknik yang digunakan pada penelitian ini adalah pre-test dan post-test yang dirancang dalam bentuk soal pilihan ganda berjumlah 10 soal. Hasil uji hipotesis pada kelompok eksperimen menunjukkan bahwa nilai thitung dengan menggunakan Equal Variences Assumed = 5.615 dan nilai Sig. (2-tailed) bernilai 0.000 serta nilai distribusi ttabel adalah 1.692, sehingga thitung > ttabel (5.615 > 1.692) dan Sig.(2-tailed) 0.000 < 0.05. Data ini menunjukkan bahwa terdapat perbedaan hasil belajar pada kelompok eksperimen dan kelompok kontrol yang disebabkan oleh perlakuan kedua kelompok yang berbeda. Berdasarkan hal tersebut dapat disimpulkan bahwa terdapat pengaruh model teams games tournament berbantuan multimedia interaktif terhadap hasil belajar aspek pengetahuan siswa SD gugus XII Kota Bengkulu.